Neuro-linguistic programming's impact on academic performance in primary schoolchildren at risk of ADHD - Furat Taha; Razan Mhanna; Zeina Harakeh; Sanaa Awada; Roula Bou Assi; Assem El-Kak; Georges Hatem (Language and Health)
This study investigates the effects of Neuro-Linguistic Programming (NLP) on students at risk of Attention Deficit Hyperactivity Disorder (ADHD), recognizing the influential role of teachers in student development. Conducted over five months in a Lebanese private school, the cohort study involved 130 students (mean age: 8.7 years) spanning grades 1–5. Utilizing the NICHQ Vanderbilt Assessment Scale, teachers' pre- and post-intervention assessments, with sociodemographic data from caregivers, were collected. Significant improvements in inattentive and hyperactive symptoms post-NLP were noted, with ADHD percentages dropping to zero. Oppositional/conduct and anxiety/depression risks also decreased. Academic performance, particularly in written expression, showed notable improvement (18–9.1 %; p = 0.05). Teachers reported substantial advancements in high-risk ADHD children following NLP interventions, highlighting the importance of teacher-student relationships, motivation, confidence, and collaborative parent-teacher efforts in creating conducive learning environments. NLP can be used as an effective tool in addressing cognitive challenges and promoting positive behavioral changes.